Coral Bleaching in Tanjung Dehegila Water, Morotai Island District - Djainudin Alwi; Iswandi Wahab; Muh Irsan (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to identify the types of corals that experience bleaching and the factors that cause it. This research was conducted in Tanjung Dehegila Waters, Morotai Island Regency, in August-September 2021. Data was collected using the Line Intercept Transect (LIT) and Photo Line Intercept Transect (LIT) methods. Observational data were analyzed descriptively. The identification results of coral bleaching species were dominated by the genus Acropora (branching corals), where species were found to be bleaching in almost all research stations, while coral bleaching in Tanjung Dehegila waters was more due to natural factors, namely high water temperatures ranging from 30-34 0C. The temperature conditions of these waters pass the optimum limit for coral reef life.